The prevalence of scapular malalignment in elementally school aged baseball player and its association to shoulder disorder - Otoshi, Kenichi; Kikuchi, Shinichi; Kato, Kinshi; Sato, Ryohei; Igari, Takahiro; Kaga, Takahiro; Konno, Shinichi (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2018)
Various shoulder disorders have been reported to be associated with scapulothoracic joint dysfunction in adult overhead athletes. However, little is known about the prevalence of scapular malalignment and its relationship to shoulder injuries in skeletally immature baseball players. The purpose of the current study was to investigate the prevalence of scapular malalignment in elementary school-aged baseball players, as well as its association with shoulder disorder. One hundred sixty-nine baseball players in higher elementary school grades (aged 11–12 years) were enrolled in this study. Shoulder pain experience pain over the previous one year, as well as other individual and environmental factors were surveyed by a self-completed questionnaire. Scapula malalignment was assessed using still images of both arms both at the side and in an elevated position. The relative position of the dominant scapula to the non-dominant side was assessed by two independent examiners. Scapular malalignment was observed in 126 subjects (74.6%), and the dominant scapula tended to deviate inferiorly and medially, as well as tilt anteriorly, compared with the non-dominant side. Forty-four of the 169 subjects (23.8%) experienced shoulder pain over the one year period. The prevalence of shoulder pain was significantly increased with the increasing scapular anterior tilt and the superior shift of the dominant scapula, whereas no significant correlation between shoulder pain and scapular horizontal shift or upward-downward rotation was observed. About three-quarters of the elementary school-aged baseball players in the current study presented with scapular malalignment, and those with anterior tilt and superior shift of the dominant scapula were at higher risk of shoulder pain.